The Income and Factors Affecting Productivity of Durian Farmers - Parniati; Andri Amaliel Managanta; Meitry Tambingsila (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Durian produces high production and quality results if an area farming well and maximizes production inputs. Durian has a considerable advantage because durian fruit has a high economic value. The study was conducted to determine the income of durian farmers and the factors that influence the productivity of durian farmers in Beraban Village. This research was conducted from April to June 2020 in Beraban Village Balinggi District Parigi Moutong Regency. The population in this study were farmers in Beraban Village who carried out durian farming, as many as 37 people. Data were taken through interviews with all farmers who were respondents. Based on the results of this study, the income of durian farmers in Beraban Village is IDR 1.743.197 per month, with an R/C ratio value of 3.52 which means that durian farming is feasible to cultivate. The factors that influence the productivity of durian farmers, namely age, formal education, and the use of appropriate phonska fertilizers, can increase the productivity of durian farmers in Beraban Village.